Elections in a democratic systems between the holiness of the concept and the usage setback - حاروش نورالدين (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2021)
When democracy was established as a system of government, it was necessary to find the appropriate mechanism that enables citizens to participate in building state institutions and participate in government, the general elections were the mechanism that allowed the people to choose their representatives. But the problem that I raise here is related to election as a concept and not as an electoral system, Which finding the appropriate formula that allows citizens to be properly represented, by implanting the election content based on choosing the best or elite (election) Therefore, the aim of this paper is to research in the content of the concept and its employability holiness by using reason and logic, which allows individuals to actively participate in building state institutions and getting a sense of belonging to the homeland, not the results of its illogical uses that contributed to misleading and spreading mediocrity and insignificance until elections became a function that lost its holiness and content These are the results obtained through this study.